A STUDY ON AWARENESS OF VARIOUS LOAN SCHEMES PROVIDED BY THE FINANCIAL INSTITUTIONS AND ITS IMPACT ON FINANCIAL INCLUSION OF BANJARA COMMUNITY WITH REFERENCE TO YAVATMAL DISTRICT - Rathod, Yogesh Ramchandra; Shetiya, Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper examines the awareness of various loan schemes provided by financial institutions and their impact on the financial inclusion of the Banjara community in the Yavatmal district. The study aims to understand the level of awareness among the Banjara community regarding these loan schemes and how this awareness influences their financial inclusion. The findings of this study will provide insights into the effectiveness of financial institutions’ outreach programs and suggest ways to enhance financial inclusion for marginalized communities.